Biochar enhanced bioaugmentation provides long-term tolerance under increasing ammonia toxicity in continuous biogas reactors. (August 2022) - Yan, Yixin; Yan, Miao; Ravenni, Giulia; Angelidaki, Irini; Fu, Dafang; Fotidis, Ioannis A.
Abstract: Bioaugmentation of ammonia-tolerant methanogens into inhibited anaerobic digestion (AD) reactors was demonstrated as an in-situ remediation strategy to alleviate ammonia toxicity. This study investigated the long-term performance of a novel bioaugmentation strategy, using gel-immobilized ammonia tolerant methanogens (biogel) enhanced with biochar to alleviate ammonia toxicity in thermophilic continuous anaerobic systems. Three ammonia shocks were applied in four continuous stirred-tank reactors, namely by adding biogel (R2 ), biochar (R3 ), both biogel and biochar (R4 ) and control reactor (R1 ), respectively. The results showed R1, R2, R3 and R4 suffered 31.3%, 28.6%, 26.0% and 17.1% methane production loss, respectively at 5.5 g NH4 + -N L −1 . R4 achieved 100% methane production recovery compared to 13% of R1 . R3 and R4 successfully acclimatized to 6.5 g NH4 + -N L −1 with 71.7% and 61.8% original methane yield compared to 36.9% and 35.6% for R1 and R2, respectively. The introduced Methanoculleus thermophilus sp. along with syntrophic partners was protected by the biochar, and its relative abundance in R4 was tenfold than R2 . Bioaugmentation developed a long-term ammonia resistance due to the synergistic interaction between biogel and biochar on alleviating ammonia inhibition, securing an additional gross profit of 11.8 $ ton −1 feedstock for the continuous biogas reactor. Graphical abstract: Image 1